Influence of Nd3+ ion on piezoelectric studies in lead barium niobate ferroelectric ceramics for device applications - D. Parajuli; N. Murali (Heliyon)
Pb₁₋ₓ₋₃y/₂BaₓReᵧ³⁺Nb₂O₆ (PBN) ceramics, where x = 0.35 and y = 0.00, 0.02, 0.04, 0.06, and Re³⁺ = Nd³⁺, were successfully synthesized using the solid-state reaction method. X-ray diffraction (XRD) analysis confirmed the formation of a pure, single-phase tetragonal structure in both undoped and Nd³⁺-modified PBN ceramics. Rietveld refinement demonstrated a strong correlation between experimental and calculated profiles, with crystallite sizes ranging from 22.6 to 25.11 nm, indicating a gradual increase in size with increasing Nd³⁺ substitution. Grain size analysis showed values between 1.09 μm and 3.95 μm, with the microstructure becoming more refined as Nd³⁺ content increased. The maximum density of 5.95 g/cm³ was achieved at y = 0.06, reflecting optimal densification from Nd³⁺ modification. Dielectric studies revealed that the phase transition temperature (Tc) followed a consistent trend, with the undoped PBN-1 showing a Tc of 350 °C, and Nd³⁺-modified compositions exhibiting lower transition temperatures of 330 °C, 315 °C, and 283 °C as Nd³⁺ content increased. The dielectric constant (Kp) reached a peak value of 0.39 at the Curie temperature and broadened with increasing Nd³⁺ content, indicating enhanced temperature stability. Furthermore, the piezoelectric coefficient (d₃₃) improved significantly with Nd³⁺ doping, reaching a maximum of 178 pC/N for y = 0.06, signifying enhanced piezoelectric performance. These results demonstrate that Nd³⁺-modified PBN ceramics are promising candidates for high-performance piezoelectric applications, particularly in environments demanding high-temperature stability and superior piezoelectric properties.